P63Long non-coding RNAs and cardiac hypertrophy. (15th July 2014) - Zhang, L; Hamad, EA; Vausort, M; Funakoshi, H; Feldman, AM; Wagner, DR; Devaux, Y
Abstract: Purpose: Long non-coding RNAs (lncRNAs) constitute a group of non-coding RNAs longer than 200 nucleotides. LncRNAs are able to regulate almost every stage of gene expression, from epigenetic modification to post-transcriptional regulation. Recent landmark studies revealed that lncRNAs are involved in cardiac development. However, the role of lncRNAs in cardiac diseases is unknown. Here, we investigated the regulation of lncRNAs in the hypertrophied heart. Methods: Wild-type and adenosine A2a receptor overexpressing mice (A2a-Tg) were subjected to transverse aortic constriction (TAC) as a model of cardiac hypertrophy or doxorubicin treatment as a model of cardiotoxicity. Hearts were harvested and expression of lncRNAs was investigated using Affymetrix Mouse Gene 1.0 ST microarrays. A specific analytical pipeline was developed to extract from these microarrays the data related to lncRNAs. Results: Analysis of microarray data identified 2 lncRNAs up-regulated and 3 down-regulated in the hearts of A2a-Tg mice subjected to TAC. Quantitative PCR showed that expression of the lncRNA 2900055J20Rik was highly down-regulated in A2a-Tg mice compared to wild-type littermates (-3.5-fold, P<0.001). To confirm the association between 2900055J20Rik and cardiac hypertrophy, we used a public microarray dataset from mice subjected to TAC. In this public dataset, expression of 2900055J20Rik was found to be up-regulated in TAC mice compared to sham-operated animals (6-fold after 28 days, P<0.01). Interestingly, administration of the BET bromodomain inhibitor JQ1, a suppressor of cardiac hypertrophy, resulted in a decrease of 2900055J20Rik expression 3, 11 and 28 days after treatment onset (P<0.01). Finally, to investigate the effect of adenosine on the expression of 2900055J20Rik in another model of cardiac stress, wild-type and A2a-Tg mice were treated with doxorubicin. As it was observed in TAC mice, expression of 2900055J20Rik was down-regulated upon overexpression of the adenosine A2a receptor in doxorubicin-treated animals (2-fold, P=0.03). Conclusions: First, we have shown that data on lncRNAs can be obtained from traditional gene expression microarrays. Second, lncRNAs are regulated in the hypertrophied heart and can be modulated by cardioprotective molecules (adenosine and JQ1). Third, we have identified the lncRNA 2900055J20Rik which may be involved in regulation of cardiac hypertrophy. These observations motivate further investigation of the therapeutic value of lncRNAs in the diseased heart.